Health status and physical activity among academic and non academic staffs in higher education - Nurul Qomariyah; Sitti Nur Djannah (Institute of Advanced Engineering and Science, 2019)
Being physically active is reducing the risk of non-communicable diseases. A cross sectional mixed method study was conducted to analyze health status and explore supporting and inhibiting factors of physical activity among academic and non academic staff in higher education. A total of 83 respondents were met the inclusion and exclusion criteria. The majority of UAD staffs are physically active and overweight. No significant health problems are found. Individual, social and environmental factors are identified as factors that can support and inhibit physical activity. Policies at the Faculty and University level are needed as well as cross-sectoral collaboration with related parties to support physical activities in UAD.